Giulio Mozzi e la realtà “avvenuta-non-avvenuta” (TEST Ticontre. Theory Text Translation, 2026)
This paper examines Giulio Mozzi’s literary work, from his early stories to Le ripetizioni (2021). Using the category of weird in a broad sense, drawing on the reflections of Mark Fisher and others, it highlights Mozzi’s constant evasion of the categories of realistic and fictional, as well as the blending of genres and registers throughout his writings. To focus on the main themes of this production, which includes short stories, essays, poems etc., some key texts are examined, in particular the ‘poetic’ collection Il culto dei morti nell’Italia contemporanea (2000 and 2018) and the collection of short stories Il male naturale (1998 and 2011): in them characters (Mario, Bianca, Santiago…) and situations emerge, often of uncertain status (real-fictitious), which will then be taken up and completed in the novel Le ripetizioni, which alludes from the title to a work by Kierkegaard known in Italy as La ripetizione (1843). Mozzi worked on it, with long interruptions, for over twenty years, ultimately proposing a montage of scenes without a precise chronological order and with a decidedly alienating overall effect. Many models have been cited, from the works of the Nouveau Roman to the film Eternal Sunshine of the Spotless Mind (2004), but the analysis focuses primarily on the narrative outcome. Overall, this text, and many others by Mozzi, raise the question of how to achieve an effective realism suited to our times, in which a notable fictional and weird component is grafted almost by necessity and in any case without fractures.